Assessing the Quantum-Computing Landscape. - DESHPANDE, ADVAIT (Communications of the ACM, 2022)
The article focuses on the impact of quantum computing and quantum communications. Topics include how quantum hardware and software being developed are fundamentally different from classical computers, the importance of a hybrid computing approach, and the need for improvements in the quality of qubits.